2022
DOI: 10.3389/fevo.2022.910260
|View full text |Cite
|
Sign up to set email alerts
|

Transient co-singing of offspring and mothers in non-duetting Javan gibbons (Hylobates moloch)

Abstract: While the vocalizations of non-human primates were thought to be innate, recent studies have revealed highly flexible vocalizations in immatures. This behavior suggests that social influences have an important role in developing vocalizations. Yet not much is known about how non-human primate vocalization develop and how the vocalizations of immature animals differ between sexes. Here, we analyzed 95 cases of co-singing between mothers and offspring out of 240 female songs from three groups of wild Javan gibbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
(70 reference statements)
0
2
0
Order By: Relevance
“…There are records of the date of birth of all offspring except for one (Salwa). To estimate the age of Salwa, the inter-birth interval of this study population was calculated from offspring whose date of birth was recorded between 2010 and 2021 (N of offspring = 7; mean ± SD = 1295 ± 242 days) and subtracted that from the date of birth of the next born individual (Sanha) 44 . Even though the paternity of the study groups was not confirmed, we had not observed any adult male replacement or extra-pair copulation since 2007, which results in three reproductive cycles of adult females in group A and B, and two cycles in group S. All study offspring except Salwa were born after the groups were followed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are records of the date of birth of all offspring except for one (Salwa). To estimate the age of Salwa, the inter-birth interval of this study population was calculated from offspring whose date of birth was recorded between 2010 and 2021 (N of offspring = 7; mean ± SD = 1295 ± 242 days) and subtracted that from the date of birth of the next born individual (Sanha) 44 . Even though the paternity of the study groups was not confirmed, we had not observed any adult male replacement or extra-pair copulation since 2007, which results in three reproductive cycles of adult females in group A and B, and two cycles in group S. All study offspring except Salwa were born after the groups were followed.…”
Section: Methodsmentioning
confidence: 99%
“…Since her date of birth was not recorded, we used the same way as the case of Salwa to estimate the age of Sendi. Since Salwa was born after Sendi, we subtracted the inter-birth interval of this study population (mean ± SD = 1295 ± 242 days) from the estimated date of birth of Salwa 44 .…”
Section: Methodsmentioning
confidence: 99%